2017
DOI: 10.5935/0101-2800.20170003
|View full text |Cite
|
Sign up to set email alerts
|

Daily variability of resting energy expenditure in acute kidney injury patients on dialysis

Abstract: Variabilidade diária do gasto energético de repouso em pacientes com lesão renal aguda em tratamento dialítico Introdução: É imprescindível a correta estimativa do gasto energético de repouso (GER), que pode apresentar considerável variação diária no paciente crítico com lesão renal aguda (LRA). Objetivo: Avaliar a variabilidade diária do GER medido por calorimetria indireta (CI) em pacientes com LRA e indicação dialítica e identificar as variáveis clínicas associadas ao GER. Métodos: O GER foi medido no dia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Fourth, this study identified several factors with no association with EE. These factors were heart rate [34,58,63,70,83,90,92,95,106,116,118,137], FiO 2 [70,90,91,138], respiratory rate [70,90,95], respiratory disease diagnosis [22,70,90], PEEP [90,138], CRP [23,52,59,91,134], size [22,51,74,109], and ICU days [22,23,113,116]. Physiologically, heart rate changes and inflammation represented by CRP result in a change in oxygen consumption and hence EE.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study identified several factors with no association with EE. These factors were heart rate [34,58,63,70,83,90,92,95,106,116,118,137], FiO 2 [70,90,91,138], respiratory rate [70,90,95], respiratory disease diagnosis [22,70,90], PEEP [90,138], CRP [23,52,59,91,134], size [22,51,74,109], and ICU days [22,23,113,116]. Physiologically, heart rate changes and inflammation represented by CRP result in a change in oxygen consumption and hence EE.…”
Section: Discussionmentioning
confidence: 99%
“…One observational study in CKD with KF patients found no difference in REE in the same cohort of patients before the beginning of dialysis (hemodialysis and PD) and one month after hemodialysis or PD initiation [179]; in the same way, critically ill patients with AKI undergoing KRT had similar REE measured by indirect calormetry than AKI patients not on KRT [142]. Only one observational study found a difference between REE of patients with AKI before the initiation of KRT and after five days on dialysis [180]. However, the study had a high dropout rate (24 patients evaluated at five days out of 124 enrolled).…”
Section: What Are the Optimal Combinations Of Carbohydrate And Lipid Calories For Medical Nutrition?mentioning
confidence: 97%